CONCEPT OF ASSESSMENT AND MANAGEMENT OF HUMAN CAPITAL AT THE ENTERPRISE (Economic journal of Lesya Ukrainka Volyn National University, 2019)
The article shows that the human role in society and social production is growing rapidly, and most importantly it is changing its quality and requirements for its existence, development and realization. In this critical aspect, the problem of human formation and development in the coordinates of social life and production in its various forms is considered. The concept of research and evaluation of qualitative characteristics of a certain human in their development is substantiated.The basis of this concept is the provision that the human being is the main value and the main source of social, economic and progressive development of any subject of economic activity. The concept is based on the unity of the three categories: the human being - as the main value, the human being - as a bearer of unique individual qualities, the human being - as a human capital. The first two categories are related to the sphere of social development and the third one is related to the sphere of production, entrepreneurship, economy of market relations.          It is considered and determined the objectivity of the origin, significance and connection of the categories "human value", "human resource" and "human capital in the aspect of improving the possibilities for the definition of more clear and grounded ways and means of ensuring the desired level of quality of life and work.     The author's vision and interpretation of the concepts of "human value", "human resource" and "human capital" are given in the article. The criteria for differentiating these concepts are defined. It is considered the foreign experience from the standpoint of using a set of important indicators and indices related to life, quality and human development. For example, it is the indicated relevance and widespread use of indicators such as the index of human intellectual development in various spheres and at different levels of social development. It is noted that the international community has developed the necessary, adequate and appropriate analytical tools for the development of such indicators that reflect all the specificity and uniqueness of the human being and ones’ personal or social status and development. It is presented the method of evaluation of the human being and human capital indicators. There are structurally determined the main components for the systematic coverage of the essence of the category "human capital of an employee of an enterprise" (the intellectual capital of an employee, the social capital of an employee, the psychological capital of an employee, organizational and creative capital of an enterprise, physiological capital of an enterprise).The method of estimating the level of human capital of an employee of an enterprise is an important element in the assessment of human capital at the enterprise level as a whole. It is concluded that the concept proposed by the author:1) allows more responsible, deep and systematic approach to the issue of researching the essence of human capital of an enterprise;2) focuses on the integrated approach in the process of formation and development of human capital of the employee of an enterprise;3) defines theoretical and methodical approaches to the assessment of human capital of the employee of the enterprise and on these principles, the formation of improved system of personnel management of the enterprise and its human capital.
Keywords: conception, value of man, human resource, human capital, estimation, management, quality.